2012
DOI: 10.3382/ps.2012-02218
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic characterization of Salmonella Enteritidis isolates on persistently contaminated layer farms during the implementation of a national control program with obligatory vaccination: A longitudinal study

Abstract: Since 2007, a national Salmonella control program including obligatory vaccination has been ongoing in Belgium. In this context, the aim of the present study was to investigate the diversity of Salmonella enterica serovar Enteritidis isolates on 5 persistently contaminated Belgian layer farms and to examine the potential sources and transmission routes of Salmonella Enteritidis contamination on the farms during successive laying rounds. A collection of 346 Salmonella isolates originating from the sampled farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Strategies have been explored in attempts to either prevent establishment of Salmonella in laying hens at various stages of the production cycle or eliminate already established Salmonella. Attempts have been made to protect birds against Salmonella using a variety of live and attenuated vaccines that were specifically designed to limit Salmonella colonization and infection in young birds via resistance immunologically [231][232][233]. As more emphasis is being placed on preharvest prevention of Salmonella colonization there will be further need to develop and expand preventative interventions such as vaccines.…”
Section: Preharvest Interventionsmentioning
confidence: 99%
“…Strategies have been explored in attempts to either prevent establishment of Salmonella in laying hens at various stages of the production cycle or eliminate already established Salmonella. Attempts have been made to protect birds against Salmonella using a variety of live and attenuated vaccines that were specifically designed to limit Salmonella colonization and infection in young birds via resistance immunologically [231][232][233]. As more emphasis is being placed on preharvest prevention of Salmonella colonization there will be further need to develop and expand preventative interventions such as vaccines.…”
Section: Preharvest Interventionsmentioning
confidence: 99%
“…Previous studies have shown that the transfer process of eggs presents a potential risk for cross-contamination (Davies and Wray, 1994). Based on multilocus variable number of tandem repeat analysis-phage typing, Dewaele et al (2012a) also suggested that cross-contamination may occur between the henhouse and egg collection areas.…”
Section: Eric-pcr Fingerprinting and Clustering Analysismentioning
confidence: 99%
“…Enteritidis isolates on five persistently S . Enteritidis contaminated Belgian layer farms in the period 2008–2011, PT4b and PT6c were predominantly isolated (Dewaele et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis isolates and the diversity of isolates before and after the implementation of the NCP. Therefore, phage typing (PT) (NRCSS, ) and Multiple‐locus variable number tandem‐repeat assay (MLVA) typing (Beranek et al., ; Dewaele et al., ) of available layer farm related S . Enteritidis isolates from 2000 to 2010 were compared with strains isolated from humans from 2002 to 2010 and both sets were collected in Belgium.…”
Section: Introductionmentioning
confidence: 99%